1986
DOI: 10.1177/030098588602300111
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and Immunohistochemical Features of Two Spontaneous Peripheral Nerve Tumors in Wistar Rats

Abstract: Abstract. Morphologic features and S-100 protein immunoreactivity of a benign and malignant peripheral nerve sheath tumor were studied in two Wistar rats. Neoplasms that developed in untreated control rats from tumor bioassays were S-100 protein positive and had similar histopathologic features. Each peripheral nerve sheath tumor was encapsulated and composed of spindle cells arranged around small thin-walled blood vessels. Palisaded tumor cells were in the benign peripheral neme sheath tumor while cells of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…However, intracranial malignant Schwannomas that were chemically induced in hooded rats had scattered pigmented cells that contained melanosomes and premelanosomes (27). Ultrastructurally, in this study, amelanotic melanoma cells were readily distinguished from neoplastic Schwann cells by the absence of the pericytoplasmic basal lamina, which is the crucial histogenetic criterion for Schwannoma cells (4,10,12,17,30).…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…However, intracranial malignant Schwannomas that were chemically induced in hooded rats had scattered pigmented cells that contained melanosomes and premelanosomes (27). Ultrastructurally, in this study, amelanotic melanoma cells were readily distinguished from neoplastic Schwann cells by the absence of the pericytoplasmic basal lamina, which is the crucial histogenetic criterion for Schwannoma cells (4,10,12,17,30).…”
Section: Introductionmentioning
confidence: 63%
“…Schwann cell tumors occur in various tissues and organs in albino rats, but the presence of premelanosomes in neoplastic Schwann cells has never been reported (4,12,17,24,30). However, intracranial malignant Schwannomas that were chemically induced in hooded rats had scattered pigmented cells that contained melanosomes and premelanosomes (27).…”
Section: Introductionmentioning
confidence: 99%
“…5,7,8,14,18,22) based on their cellular pleomorphism, anaplasia, increased mitoses, and local invasion. Malignant forms of schwannoma were poorly circumscribed and infiltrative.…”
Section: Resultsmentioning
confidence: 99%
“…7,12 Macroscopically, benign animal schwannomas are usually encapsulated, globoid, lobulated masses of variable size and shape, depending on location of the neoplasm and animal species affected. 1,4,5,[15][16][17] Malignant schwannomas are usually nonencapsulated and infiltrative tumors. Microscopically, the classical description of schwannoma is characterized by Antoni type A and B patterns and Verocay body formation.…”
mentioning
confidence: 99%
“…Shiga et al [27] reported a HB in a dog to be positive for NSE, but no neuroendocrine granules were observed on electron microscopic examination. S-100 protein is known to be expressed in many neuroectodermal tissues or neoplasms, as well as various other mesenchymal tissues/tumors [2,9,15,35]. Since, in the present study, mouse HBs were negative for vimentin and there are no studies with immunoreactivity for NSE and electron microscopic features, the significance of the S-100 protein expression remains unclear.…”
Section: Discussionmentioning
confidence: 65%